Impact of Pre-existing Type 2 Diabetes Mellitus and Cardiovascular Disease on Healthcare Resource Utilization and Costs in Patients With COVID-19 - Chi Nguyen; Christopher L. Crowe; Effie Kuti; Bonnie Donato; Rachel Djaraher; Leo Seman; Nancy Graeter; Thomas P. Power; Rinku Mehra; Vincent J. Willey (Journal of Health Economics and Outcomes Research)
**Background:** The economic burden associated with type 2 diabetes mellitus (T2DM) and concurrent cardiovascular disease (CVD) among patients with COVID-19 is unclear.